MP07: Diagnosis of elevated intracranial pressure in critically ill adults – a systematic review and meta-analysis. (May 2019) - Fernando, S.; Tran, A.; Cheng, W.; Rochwerg, B.; Taljaard, M.; Kyeremanteng, K.; English, S.; Sekhon, M.; Griesdale, D.; Dowlatshahi, D.; Czosnyka, M.; McCredie, V.; et al.
Abstract : Introduction : Elevated intracranial pressure (ICP) is a devastating complication of brain injury, such as traumatic brain injury, subarachnoid hemorrhage, intracerebral hemorrhage, ischemic stroke, and other conditions. Delay to diagnosis and treatment are associated with increased morbidity and mortality. For Emergency Department (ED) physicians, invasive ICP measurement is typically not available. We sought to summarize and compare the accuracy of physical examination, imaging, and ultrasonography of the optic nerve sheath diameter (ONSD) for diagnosis of elevated ICP.Methods : We searched Medline, EMBASE and 4 other databases from inception through August 2018. We included only English studies (randomized controlled trials, cohort and case-control studies). Gold standard was ICP≥20 mmHg on invasive ICP monitoring. Two reviewers independently screened studies and extracted data. We assessed risk of bias using Quality Assessment of Diagnostic Accuracy Studies 2 criteria. Hierarchical Summary Receiver Operating Characteristic model generated summary diagnostic accuracy estimates.Results : We included 37 studies (n = 4, 768